Raising awareness on mental health in the heliophysics community - Nikoukar, Romina; Regoli, Leonardo; Halford, Alexa J.; Zettergren, Matthew D.; Dialynas, Konstantinos; Filwett, Rachael (Frontiers in Physics, 2023)
To foster greater diversity, equity, and inclusion within the field of space sciences, it is crucial that we recognize and proactively address the mental health challenges experienced by our community. The purpose of this article is to raise awareness about mental health, assess the current state of our community in this regard, and explore ways to better safeguard and support our community members. We present a compelling argument for conducting surveys to evaluate the mental health and overall well-being of our community. Additionally, we offer several recommendations aimed to improve the mental health within our research community such as promoting honest conversations and programs on stress management and resilience building, training to notice and respond, and rethinking sick days. We recommend reevaluating our definition of success and reconsidering the existing strategies aimed at addressing the issues related to power imbalances. By promoting mental health awareness, fostering an open and supportive culture, and implementing policies that prioritize the well-being of all individuals, we can create an environment that is more inclusive and conducive to the thriving of every member.